Waste less time on Facebook — follow Brilliant.
×

Algebra

If \(x+\dfrac{1}{x}=1\) ,then the value of \(x^{12}+x^9+x^6+x^3+1\) is?

Note by Gautam Arya
3 months, 2 weeks ago

No vote yet
1 vote

  Easy Math Editor

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 \( 2 \times 3 \)
2^{34} \( 2^{34} \)
a_{i-1} \( a_{i-1} \)
\frac{2}{3} \( \frac{2}{3} \)
\sqrt{2} \( \sqrt{2} \)
\sum_{i=1}^3 \( \sum_{i=1}^3 \)
\sin \theta \( \sin \theta \)
\boxed{123} \( \boxed{123} \)

Comments

Sort by:

Top Newest

\(\begin{align} x+\dfrac{1}{x}&=1 \hspace{5mm}\color{blue}\text{given}\\ \implies x^2-x+1&=0 \\\\ \text{Multiplying both sides} &\text{with x+1,we get,}\\ x^3+1&=0\\ \implies x^3&=-1\\ \text{Substituting for}&x^3 \text{we get}\\ 1+x^3+x^6+x^9+x^{12}&=1-1+1-1+1=\boxed{1}\end{align} \)

Anirudh Sreekumar - 3 months, 2 weeks ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...